Cent ans de silence ? Sur les traces du Parti des Indépendants de Couleur à Cuba dans les expressions musicales populaires d’Oriente (1912-2022) : évolutions et métamorphoses - Lévana Garçon (Caravelle)
This article aims to question the silence around the memory of the Partido de Independientes de Color (PIC) massacre following the tracks left by the inaudible voices of Oriente in regional popular music. The goal of this article is to observe how this memory acts from the margins and how it metamorphoses and resignifies the event over time.